Primary and Secondary Attack Rates by Vaccination Status after a SARS-CoV-2 B.1.617.2 (Delta) Variant Outbreak at a Youth Summer Camp—Texas, June 2021. Issue 12 (31st August 2022) - Baker, Julia M; Shah, Melisa M; O'Hegarty, Michelle; Pomeroy, Mary; Keiser, Philip; Ren, Ping; Weaver, Scott C; Maknojia, Sara; Machado, Rafael R G; Mitchell, Brooke M; McConnell, Allan; Tate, Jacqueline E; et al.
Abstract: Children are capable of initiating COVID-19 transmission into households, but many questions remain about the impact of vaccination on transmission. Data from a COVID-19 Delta variant outbreak at an overnight camp in Texas during June 23–27, 2021, were analyzed. The camp had 451 attendees, including 364 youths aged  < 18 years and 87 adults. Detailed interviews were conducted with 92 (20.4%) of consenting attendees and 117 household members of interviewed attendees with COVID-19. Among 450 attendees with known case status, the attack rate was 41%, including 42% among youths; attack rates were lower among vaccinated (13%) than among unvaccinated youths (48%). The secondary attack rate was 51% among 115 household contacts of 55 interviewed index patients. Secondary infections occurred in 67% of unvaccinated household members and 33% of fully or partially vaccinated household members. Analyses suggested that household member vaccination and camp attendee masking at home protected against household transmission. Abstract : Vaccination can limit SARS-CoV-2 transmission among youth in congregate settings and can be used with mitigation measures to decrease secondary transmission.